Health-related benefits: their influence on loyalty and physical activity participation in Australian public aquatic centres. (1st January 2012) - Howat, Gary; Alikaris, Jessica; March, Heather; Howat, Peter
The present study aimed to examine health-related benefits and their potential role in encouraging more people to undertake regular physical activity at public aquatic centres. The study used the service quality – overall satisfaction – loyalty model to examine outcome service quality, especially health-related benefits, and their influence on loyalty (WOM recommendation), mediated by overall customer satisfaction. Based on a sample of 7, 133 customers of 27 multi-purpose public aquatic centres in Australia, regression analyses indicated that health-related benefits dimensions, improved health and fitness and relaxation and stress release, had the greatest influence on overall customer satisfaction, which in turn significantly influenced word-of-mouth recommendation. Improved health and fitness was also rated highest for benefit importance as well as benefit attainment, with success in competition the lowest rated benefit dimension. Further research is recommended to clarify the role of health-related benefits in facilitating physical activity, thus reducing the prevalence of chronic health disease.